RETROSPECTIVE ANALYSIS OF FREIGHT CARS REPAIR ORGANIZATION METHODS IN THE DEPOT AND THE WAYS OF THEIR FURTHER DEVELOPMENT - Myamlin, V. V. (Science and Transport Progress, 2010)
A critical analysis of existing methods for repair of freight wagons is presented. The conclusion, that with probability nature of repair activities the “classic” type of a “rigid” production line with regulated step in long-term outlook is inexpedient, has been done. The further development of production-line wagon repair activities is seen in the creation of advanced enterprises equipped with multi-object flexible asynchronous systems with high level of mechanization and automation of technologic processes.